Ucieknijmy od niej - Koszałka, Marcin (Poland : HBO Poland, 2010)
The filmmaker goes back to the personal family thread initiated in his previous film "Such a Beautiful Son I Delivered" and creates a new intimate documentary devoted to family matters, only this time, seen through the eyes of his sister. "Let's Run Away From Her" is in its first layer a portrait of his sister: a luxurious businesswoman. The sister loves life and the world, but only its beautiful form. By following her, little by little, more layers of difficult family relations and ambiguous personalities are revealed.
Keywords: Poland